The Influence of Youtube Learning Media on Learning Outcomes in Economics Subject Class X IPS Students of SMA Negeri 5 Pematang Siantar Academic Year 2022/2023 - Putri Indah Sari Sinaga; Rosma Simangunsong; Anggun Tiur Ida Sinaga (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the influence of YouTube media on student learning outcomes in economics subjects for class X IPS students at SMA Negeri 5 Pematang Siantar. This type of research is a quantitative research with a quantitative descriptive data analysis approach. The population of the study was the X IPS class students at SMA Negeri 5 Pematang Siantar with a total of 172 people. The research sample was 72 people. The sampling technique used was purposive sampling technique. The data collection technique used was a questionnaire (questionnaire). The hypothesis-taking technique uses simple linear regression analysis and the coefficient of determination (R2). The results of the study are that there is a positive and significant influence between YouTube learning media on the economics learning outcomes of class X IPS students at SMA Negeri 5 Pematang Siantar, namely a significant value of 0.693 > 0.05. Youtube Media R2 test has an effect of 0.003 x 100%, which means that the effect of the independent variable (X) on the dependent variable (Y) is 0.3% and the remaining 97.7% is influenced by variables not included in this study.